The Burden : African Americans and the Enduring Impact of Slavery - Auslander, Mark; Hannah-Jones, Nikole; Riley, Rochelle (Book collections on Project MUSE., 2018)
This book is a plea to America to understand what life post-slavery remains like for many African Americans, who are descended from people whose unpaid labor built this land, but have had to spend the last century and a half carrying the dual burden of fighting racial injustice and rising above the lowered expectations and hateful bigotry that attempt to keep them shackled to that past.